Comprehensive Midwifery Care For Mrs. D At Aliyah Tami Bpm, Jl. Rakuta Sembiring, Pematang Siantar - May Linda Kristina; Sri Rahma Friani (International Journal of Health Engineering and Technology, 2025)
Comprehensive midwifery care, or Continuity of Care (CoC), is vital for reducing maternal and infant mortality rates, which remain a significant public health issue globally and in Indonesia. This study aims to demonstrate the practical application and effectiveness of a continuous care model in a real-world midwifery setting.This case study aims to provide and implement comprehensive midwifery care for a client, Mrs. D, to document the outcomes and adherence to clinical standards throughout the entire maternal and neonatal continuum. A qualitative case study approach was used, focusing on a single subject, Mrs. D (G3P3A0), at BPM Aliyah Tami. Data was collected from February to March 2025 through direct observation, in-depth interviews, and physical examinations. The care was managed using Varney’s framework and documented with the SOAP method. The data was analyzed descriptively to narrate the client's journey and care outcomes.The comprehensive care provided led to a successful physiological pregnancy, a normal spontaneous delivery at 37 weeks' gestation with no complications, and a healthy newborn. The mother's postpartum recovery was physiological, and she successfully adopted a family planning method. All stages of care were consistent with established midwifery standards.The implementation of a comprehensive midwifery care model ensures positive outcomes for both mother and baby. The study's findings affirm that continuous, structured care is a cornerstone of safe and effective midwifery practice.